A Review of Toulmin's Argumentation in Mathematics dan Science Learning: Implementation, Impact and the Role of the Teacher - Badjeber, Rafiq; Supriyatman, Supriyatman; Afadil, Afadil; Hadi, Windia (Jurnal Pendidikan MIPA, 2024)
A Review of Toulmin's Argumentation in Mathematics dan Science Learning: Implementation, Impact and the Role of the Teacher. Objective: This review study aims to analyze and provide a complete study of the role of Toulmin's argumentation model in math and science learning Methods: This study uses a systematic literature review by following the PRISMA form. We found 396 documents on the Toulmin’s argumentation model published in 2020-2024, which were collected through the Scopus database. After the screening process, 19 articles were selected for analysis using thematic analysis. Findings: The review findings show that Toulmin's argumentation model is flexible enough to be used in learning, either as an argumentation analysis tool or as part of an innovative learning design. The positive impact can be seen in improving students' critical thinking skills, conceptual understanding, reasoning, and justification abilities. In addition, teachers have a vital role in supporting students' argumentation. The teacher is a facilitator, guide, and feedback provider that helps students develop and effectively deliver arguments. Conclusion: This study confirms that Toulmin's argumentation is relevant to improving students' higher-order thinking skills. It highlights the need for professional development for teachers to optimally support argumentation-based learning and select the most appropriate ways of integrating scientific argumentation into learning practice.        Keywords: mathematics learning, role of teacher, science learning, student's skills, toulmin's argumentation.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1199-1213